Developing multi-omics approaches for the study of extendedspectrum β-lactamase-producing Escherichia coli and vancomycin-resistant Enterococcus faecalis strains from clinical source - Pinto, Luís Carlos Rodrigues Carvalho (2020)
Genomics, transcriptomics and proteomics tools generate enormous amounts of biological data properly processed through bioinformatics. The integration of all this interdisciplinary data is a valuable asset for a greater understanding of biological systems that negatively impact the human healthcare and ultimately leading to the development of new and improved therapeutical strategies. The crescent public health concern of antibiotic resistant bacteria found in clinical environment is, nowadays, one of the major problems for the healthcare systems worldwide and so, therefore, consists as a vital candidate for an omics approach. Escherichia coli and Enterococcus faecalis are among the most frequent commensal inhabitants of the gastrointestinal tract of humans that currently have also been largely associated to the problematic of antibiotic resistance as cause for multiple cases of varied infections. The main focus of this thesis consisted in the application of omics methodologies in order to assess, in a first stage, the antibiotic resistance and virulence nature of Escherichia coli and Enterococcus faecalis strains found in human patients. In a second stage, was intended to submit a multidrug-resistant Enterococcus faecalis strain of clinical source to different antibiotic stresses with the purpose of understanding the changes in the resistance mechanisms. Initially, the expression of whole cell proteome and different sub-proteomes was determined by the use of 2-DE and MALDI-TOF/MS analysis and, on the other hand, a total RNA analysis was conducted through whole-genome sequencing (WGS) followed by RNA sequencing. This set of methodologies was applied to the study of an extendedspectrum β-lactamase Escherichia coli strain (C999) and a vancomycin-resistant Enterococcus faecalis strain (C2620), resulting in an extensive quantification, identification and characterization of both transcripts and proteins. This study revealed the expression of several transcripts/proteins related to antibiotic resistance and various types of stress response factors, as well as features linked to cell survival, endurance towards different environments and transport/propagation, which is extremely relevant considering the pathogenic nature of the strains studied and its relation to the hospital environment. Finally, the integration of both proteomic and transcriptomic data allowed to conduct a deep comparison of the different types of expression, reinforcing the conclusions resultant from this study. The following step of this research was to submit a vancomycin-resistant Enterococcus faecalis strain (C2280) to various sub-inhibitory concentrations of vancomycin and gentamicin. The effects of these stress conditions were then evaluated for total transcriptome expression through WGS and RNA sequencing whereas total proteome analysis was conducted by iTRAQ labeling coupled with reverse-phase peptide fractionation and 1-D-nano LC ESI-MSMS. This approach resulted in the quantification, identification and characterization of proteins and transcripts resultant from the different stress conditions applied. Comparing with the initial approach applied in this study, the use of iTRAQ allowed to increase the amount and accuracy of the obtained data, and it also showed to be highly relevant to study the expression of the different stress proteomes by allowing to determine the alterations in the expression levels resultant from each stress. Overall, this thesis discussed the application of genomic, transcriptomic and proteomic tools to the study of multidrug-resistant Escherichia coli and Enterococcus faecalis clinical strains for determining the presence of antibiotic resistance and various stress response factors. In fact, the use of different methodologies and techniques abroad these three areas of science have made a major contribution to a greater understanding of the mechanisms of resistance, stress response and others that ensure the survival and endurance of such microorganisms in clinical environment as well as the spreading abilities of these bacteria. Finally, this work demonstrated the relevance of the integration of data obtained from different omics tools as a major asset for addressing the growing antibiotic resistance issue providing a closer look on the functioning of the cellular mechanisms of multi-resistant bacteria.